The growth performance and resistance to salinity stress of striped catfish Pangasius sp. juvenile in biofloc system with different feeding rates - Wellya Wichi Meritha; Muhammad Agus Suprayudi; Julie Ekasari (Jurnal Akuakultur Indonesia)
ABSTRACT